Ionic exchange desorption of mercury from contaminated dredging sludge (at 393K and ambient temperature). Issue 1 (2nd January 2019) - Comuzzi, Clara; Ballico, Maurizio; Aneggi, Eleonora; Rubio Aleman, Maria Jose; Conesa Perez, Gabriel Jose; Fattori, Andrea; goi, Daniele
ABSTRACT: In this work, we reported results obtained during experimental tests to introduce a new approach to the treatment of dredging sludge polluted by mercury. A slurry of dredging sludge was treated by cationic exchange procedures both at ambient temperature and distilled at 393K with the aid of some different exchange salts: three inorganic (NaCl, CaCl2, and CaI2 ) and two organic Tetrabutylammonium chloride [(C4 H9 )4 NCl] and Ethyl Viologen diiodide (1, 1′-Dietil-4, 4′-bipyridinium diiodide) [C14 H18 I2 N2 ], having different cationic exchangeable part and different molecular weights. A similar (15% w/w) solution was used to treat mercury-polluted sludge considering 2, 24, and 48 h of reaction time. The removal efficiencies of the inorganic/low molecular weight monovalent salts were minimal at the tested temperatures, while higher removal was reached when CaI2 and Viol-I2 were used at ambient temperature with maximum treatment efficiencies over 70% in 48 h treatment. A recovery/reuse of the exchanging solutions was also tested finding good recovery potential of the salt slurry.